NC-Smarandache Ruled Surface and NW-Smarandache Ruled Surface according to Alternative Moving Frame in E3 - Soukaina Ouarab (Journal of Mathematics)
In this study, original definitions of NC−Smarandache ruled surface and NW−Smarandache ruled surface according to the alternative moving frame are introduced in E3. The main results of the study are presented in theorems that give necessary and sufficient conditions for those special surfaces to be developable and minimal. Finally, an example with illustrations is presented.